KOMODITI YANG DISEBUT MANUSIA: Membaca Fenomena Perdagangan Manusia di NTT dalam Pemberitaan Media - Robert Mirsel; Yohanes Celvianus Manehitu (Institut Filsafat dan Teknologi Kreatif Ledalero, 2014)
This article describes and analyzes human trafficking in East Nusa Tenggara Province (NTT) based on the news/data exposed by two local newspapers, Pos Kupang and Flores Pos, during the past four years (2010-2013). Employing media analysis (content analysis), the exploration of various news items on human trafficking in the two newspapers shows a significant increase in the number of cases in the province. Victims are mostly poor, of different ages but mainly women and children. Many agents played an important role and have employed various modes for recruiting victims. The main root of human trafficking in NTT is the system which allows the agents/actors of recruitment of migrant workers (PJTKI) to operate illegally in the province; individuals are victims of this system of recruitment. This study recommends that there should be a significant change in the system of recruitment and control in the NTT province in particular, and in Indonesia in general, to prevent and overcome the problem of human trafficking along with other efforts to empower the local people economically, socially and culturally by enhancing their knowledge, skills and mentality so that they are able to defend their own rights when being victimized by recruiters, whether individual agents or recruiting companies. Kata-kata kunci: Perdagangan manusia, analisis isi, korban, cara merekrut, rekrutmen ilegal, agen ilegal, pekerja migran ilegal, sistem rekrutmen dan kontrol.